Investigating the genetic basis of attention to facial expressions: the role of the norepinephrine transporter gene. (December 2016) - Yang, Xing; Ru, Wenzhao; Wang, Bei; Gao, Xiaocai; Yang, Lu; Li, She; Xi, Shoumin; Gong, Pingyuan
Abstract : Objective: Levels of norepinephrine (NE) in the brain are related to attention ability in animals and risk of attention-deficit hyperactivity disorder in humans. Given the modulation of the norepinephrine transporter (NET) on NE levels in the brain and the link between NE and attention impairment of attention-deficit hyperactivity disorder, it was possible that the NET gene underpinned individual differences in attention processes in healthy populations. Methods: To investigate to what extent NET could modulate one's attention orientation to facial expressions, we categorized individuals according to the genotypes of the −182 T/C (rs2242446) polymorphism and measured individuals' attention orientation with the spatial cueing task. Results: Our results indicated that the −182 T/C polymorphism significantly modulated attention orientation to facial expressions, of which the CC genotype facilitated attention reorientation to the locations where cued faces were previously presented. However, this polymorphism showed no significant effects on the regulations of emotional cues on attention orientation. Conclusion: Our findings suggest that the NET gene modulates the individual difference in attention to facial expressions, which provides new insights into the roles of NE in social interactions.